2019
DOI: 10.1186/s12911-019-0991-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying undetected dementia in UK primary care patients: a retrospective case-control study comparing machine-learning and standard epidemiological approaches

Abstract: BackgroundIdentifying dementia early in time, using real world data, is a public health challenge. As only two-thirds of people with dementia now ultimately receive a formal diagnosis in United Kingdom health systems and many receive it late in the disease process, there is ample room for improvement. The policy of the UK government and National Health Service (NHS) is to increase rates of timely dementia diagnosis. We used data from general practice (GP) patient records to create a machine-learning model to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…While recent reviews of dementia risk prediction models show a large body of research on methods to predict likelihood of dementia at a future point 22, 23 , we found few studies that aimed to model automated methods to detect current, early dementia, especially in primary care or using only primary care data 24,25 . So far, there has been little investigation of how accurate an early detection model using only primary care data could be to pick up dementia, or how much earlier than current diagnosis by GPs a tool could discriminate well between patients who go on to be diagnosed and those who do not.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…While recent reviews of dementia risk prediction models show a large body of research on methods to predict likelihood of dementia at a future point 22, 23 , we found few studies that aimed to model automated methods to detect current, early dementia, especially in primary care or using only primary care data 24,25 . So far, there has been little investigation of how accurate an early detection model using only primary care data could be to pick up dementia, or how much earlier than current diagnosis by GPs a tool could discriminate well between patients who go on to be diagnosed and those who do not.…”
Section: Introductionmentioning
confidence: 95%
“…We constructed a case-control dataset. For this project, CPRD extracted the full records of patients with dementia (cases), identified on the basis of a code list for dementia diagnostic codes (general dementia, vascular and Alzheimer's dementia codes) developed using code lists from Russell et al 27 , and Rait et al 28 , and used in Ford et al 24 , (Appendix 1, see Extended data 29 ). Patients had to be 65 years or older, and had to have records available in CPRD for at least three years prior to the first diagnosis code for dementia, which was recorded between 2000 and 2012.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…be found elsewhere (55) and the full list of variables is given in Appendix 3 (Supplementary Material).…”
Section: Datasetmentioning
confidence: 99%